2013
DOI: 10.3390/md11061763
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Dynamic Changes in Proteins Associated with the Cellular Cytoskeleton after Exposure to Okadaic Acid

Abstract: Exposure of cells to the diarrhetic shellfish poison, okadaic acid, leads to a dramatic reorganization of cytoskeletal architecture and loss of cell-cell contact. When cells are exposed to high concentrations of okadaic acid (100–500 nM), the morphological rearrangement is followed by apoptotic cell death. Okadaic acid inhibits the broad acting Ser/Thr protein phosphatases 1 and 2A, which results in hyperphosphorylation of a large number of proteins. Some of these hyperphosphorylated proteins are most likely k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Combined with down-regulation of annexins and actin-related protein 2, 3, we speculated that P. lima and associated DSP toxins might induce cytoskeletonal disorganization of mussel gills. Actually, OA-induced changes in cytoskeletal architecture and cellecell contact have been extensively reported (Leira et al, 2001;Espiña and Rubiolo, 2008;Vale and Botana, 2008;Vilariño et al, 2008;Espiña et al, 2010;Wang et al, 2011;Hanana et al, 2012;Huang et al, 2013;Opsahl et al, 2013). Using a mussel cDNA microarray, Manfrin et al (2010) found that 9% of up-regulated transcripts in mussel induced by OA exposure were potentially involved in cytoskeleton organization.…”
Section: Discussionmentioning
confidence: 96%
“…Combined with down-regulation of annexins and actin-related protein 2, 3, we speculated that P. lima and associated DSP toxins might induce cytoskeletonal disorganization of mussel gills. Actually, OA-induced changes in cytoskeletal architecture and cellecell contact have been extensively reported (Leira et al, 2001;Espiña and Rubiolo, 2008;Vale and Botana, 2008;Vilariño et al, 2008;Espiña et al, 2010;Wang et al, 2011;Hanana et al, 2012;Huang et al, 2013;Opsahl et al, 2013). Using a mussel cDNA microarray, Manfrin et al (2010) found that 9% of up-regulated transcripts in mussel induced by OA exposure were potentially involved in cytoskeleton organization.…”
Section: Discussionmentioning
confidence: 96%
“…It has been described that this group of toxins can behave as both cell death inducers and tumor promoters [20]. Del Campo et al [2] stated that this dual effect of OA depends on the administered dose and applied exposure time, since in gastric epithelium (AGS and MKN45) and colon epithelium (Caco 2) models, sublethal doses of OA promote cell proliferation and activate oncogenic pathways [2]; however, only the effects on tumoral cells were studied herein, and nontumoral cells were excluded from it.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, other investigations have been attempted to link changes in cytoskeleton components with volume changes, and, more interestingly, to verify if drug-induced alterations of cytoskeleton affect cell volume regulation processes. 30 In addition, non-lytic doses of crude venom from Pelagia noctiluca directly induce mitochondrial trans-membrane potential collapse and generation of reactive oxygen species (ROS) in neuronal-like (SH-SY5Y) cells. 15 Mitochondrial membrane alterations are possibly due to Article Figure 4.…”
Section: Discussionmentioning
confidence: 99%